2022
DOI: 10.2196/preprints.43110
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What Does DALL-E 2 Know About Radiology? (Preprint)

Abstract: UNSTRUCTURED Generative models such as DALL-E 2 could represent a promising future tool for image generation, augmentation, and manipulation for artificial intelligence research in radiology provided that these models have sufficient medical domain knowledge. Here we show that DALL-E 2 has learned relevant representations of X-ray images with promising capabilities in terms of zero-shot text-to-image generation of new images, continuation of an image beyond its original boundaries, or r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Since the Large Language Models (LLMs) ChatGPT and GPT-4 were released in November 2022 and March 2023 respectively, multiple studies have shown how these LLMs could be applied to a variety of radiological tasks such as structured reporting, question answering on a radiology board-style examination, and response to common lung cancer questions (6)(7)(8). Closely related to our work, GPT-4 was shown to generate impressions for radiology reports (9).…”
Section: Introductionmentioning
confidence: 64%
“…Since the Large Language Models (LLMs) ChatGPT and GPT-4 were released in November 2022 and March 2023 respectively, multiple studies have shown how these LLMs could be applied to a variety of radiological tasks such as structured reporting, question answering on a radiology board-style examination, and response to common lung cancer questions (6)(7)(8). Closely related to our work, GPT-4 was shown to generate impressions for radiology reports (9).…”
Section: Introductionmentioning
confidence: 64%
“…However, they are mainly trained on textual datasets, and the safety issues exposed are limited to the NLP field. Recently, with the rise of multimodal pre-training models (e.g., NÜWA [153], DALL-E2 [110], GauGAN2 [119], etc. ), AI technology has demonstrated the powerful cross-modal (text-image) creation ability.…”
Section: Multimodal Information Processingmentioning
confidence: 99%
“…Numerous articles have highlighted several potential uses of GPT-4 in clinical medicine. These applications include creating virtual assistants in different kinds of surgery such as bariatric surgery, oral and maxillofacial surgery and colorectal surgery or converting unstructured radiology reports into structured formats [35][36][37][38].…”
Section: Applications Of Chatgpt and Gpt-4 In Medical And Dental Surgerymentioning
confidence: 99%